Encyclia × tixtlensis (Orchidaceae: Laeliinae), a possible natural hybrid between E. meliosma and E. atrorubens in Guerrero, México - León-Peralta, Cekouat E.; Salmerón-Barrera, Edgar; Peréz-García, Eduardo A. (Phytotaxa, 2023)
Encyclia × tixtlensis, a possible natural hybrid between E. atrorubens and E. meliosma recently found in the State of Guerrero, Mexico, is described and illustrated. Aspects of its possible hybrid origin are discussed, and a comparison is made with other Encyclia taxa found in the same region. The conical-piriform shape of its pseudobulbs, the straight or slightly reflexed leaves, as well as its flowers with light to dark brown sepals and petals, the lip with wide lobes, brown at its base and profusely magenta-streaked, and the column with a bending in the basal third, distinguish it from any other taxon in the genus.